Mesenchymal stem cell-conditioned media ameliorate diabetic endothelial dysfunction by improving mitochondrial bioenergetics via the Sirt1/AMPK/PGC-1α pathway. - Yuan, Y.; Shi, M.; Li, L.; Liu, J.; Chen, B.; Chen, Y.; An, X.; Liu, S.; Luo, R.; Long, D.; Zhang, W.; Newsholme, Philip; et al. (2016)
Vasculopathy is a major complication of diabetes. Impaired mitochondrial bioenergetics and biogenesis due to oxidative stress are a critical causal factor for diabetic endothelial dysfunction. Sirt1, an NAD(+)-dependent enzyme, is known to play an important protective role through deacetylation of many substrates involved in oxidative phosphorylation and reactive oxygen species generation. Mesenchymal stem cell-conditioned medium (MSC-CM) has emerged as a promising cell-free therapy due to the trophic actions of mesenchymal stem cell (MSC)-secreted molecules. In the present study, we investigated the therapeutic potential of MSC-CMs in diabetic endothelial dysfunction, focusing on the Sirt1 signalling pathway and the relevance to mitochondrial function. We found that high glucose-stimulated MSC-CM attenuated several glucotoxicity-induced processes, oxidative stress and apoptosis of endothelial cells of the human umbilical vein. MSC-CM perfusion in diabetic rats ameliorated compromised aortic vasodilatation and alleviated oxidative stress in aortas. We further demonstrated that these effects were dependent on improved mitochondrial function and up-regulation of Sirt1 expression. MSC-CMs activated the phosphorylation of phosphoinositide 3-kinase (PI3K) and protein kinase B (Akt), leading to direct interaction between Akt and Sirt1, and subsequently enhanced Sirt1 expression. In addition, both MSC-CM and Sirt1 activation could increase the expression of peroxisome proliferator-activated receptor γ co-activator-1α (PGC-1α), as well as increase the mRNA expression of its downstream, mitochondrial, biogenesis-related genes. This indirect regulation was mediated by activation of AMP-activated protein kinase (AMPK). Overall our findings indicated that MSC-CM had protective effects on endothelial cells, with respect to glucotoxicity, by ameliorating mitochondrial dysfunction via the PI3K/Akt/Sirt1 pathway, and Sirt1 potentiated mitochondrial biogenesis, through the Sirt1/AMPK/PGC-1α pathway.